Stational cointegration in the demand of money for transactions, Peru: 1991-2014 - Huacani Sucasaca, Yudy (2017)
The demand for long and short term real balances for Peru is theoretically consistent and empirically robust using the seasonal cointegration methodology. The stability of this function is of paramount importance for the management of monetary policy. The study uses quarterly data for the period from the fourth quarter of 1991 to the first quarter of 2014; considers a demand for money based on a scale variable representative of the income of the economy, interest rate in national currency and nominal exchange rate. The coefficients of income elasticity, interest rate and exchange rate vary in sign and magnitude depending on the theory. The long-term model and the mechanism of error correction using the short-term models exceed statistical tests, whereas the chow and cusum squared tests explain that the demand for money is a stable function. The exogeneity analysis of the regressors shows the existence of weak, strong exogeneity and superexogeneity. The predictive capacity of the seasonal cointegration model shows superiority with respect to the standard cointegration model, which allows to conclude that they are efficient to make forecasts.